UNDERSTANDING THE NEXUS OF FINANCIAL LITERACY AND BEHAVIORAL BIASES IN INVESTMENT DECISIONS - Agus Joharudin (UIN Sunan Gunung Djati Bandung, 2023)
In an era marked by an increasingly complex and dynamic financial landscape, the intersection of financial literacy, behavioral biases and investment decisions stands as a critical link influencing the economic well-being of individuals. The aim of this study is to determine the influence of financial literacy and behavioral biases on investment decisions. This study used an online questionnaire for management students of UIN Sunan Gunung Djati Bandung. It used a quantitative approach and associative design and used multiple linear regression for analysis. The study confirms that behavioral biases are present in the investment decision-making of the students. Along with financial literacy, it also significantly influences the investment decision. The study highlights the significance of financial literacy in shaping the financial stability of students. It also made aware of the potential adverse effect of behavioral biases in influencing investment decisions among investors.